Pencegahan Tawuran Antar Pelajar Melalui Pendekatan Restorative Justice - Laura, Race Nensy (Proceedings Series on Social Sciences & Humanities, 2024)
Inter-school brawls are a disturbing phenomenon in Indonesia. Various efforts have been made to prevent these brawls, but they still occur frequently. The restorative justice approach offers an alternative solution to prevent fights by focusing on restoring relationships and building a sense of responsibility. This article aims to examine the concept of restorative justice and how this approach can be applied in preventing brawls between students. The research method used in normative juridical with primary data in the form of laws and regulations and secondary data in the form of journals and articles. The result showed that brawl prevention can be done through restorative justice. The conclusion of this study is a promising approach in preventing brawls between learners.